Graduate student experience in focus: a photovoice investigation of physical and health education graduate students in Canada. (1st November 2020) - Lorusso, Jenna R.; Johnson, Ashley M.; Morrison, Hayley J.; Stoddart, Alexandra L.; Borduas, Christopher; Cameron, Nicole; Lim, Christopher; Price, Caitlin
ABSTRACT: Background: Over the past couple decades, concerns have been raised regarding graduate student wellbeing and attrition in Canada and abroad. Although research on graduate education has increased in response to these concerns, these works are often focused upon a narrow aspect of the multifaceted reality of graduate education and have not been student-conducted. This situation is largely mirrored in the case of physical education (PE), although further complicated by the focus on the United States in which graduate programmes differ considerably from Canada, Europe, and elsewhere. Purpose/Aim: The purpose of this research was to conduct a broad investigation into our own experiences as PE graduate students in Canada. Two research questions guided our team of eight Canadian-based PE graduate students: What are our experiences as PE graduate students in Canada? How might we enhance the experience for ourselves and others like us? We hoped that if we worked together to better understand and thrive in our situations, we might develop a supportive peer community and be able to promote positive changes to PE graduate education. Design: Drawing upon the participatory research method of photovoice, we individually took photographs of our graduate experiences and then engaged in critical discussions about the meaning, conditions, and possibilities of those experiences. These discussions were analysed in an iterative process of independently and collaboratively coding, thematizing, and refining to produce themes of our experiences. Guided by the criteria of continuity and interaction in Dewey's theory of experience, we engaged in an interpretive analysis of the themes in terms of their educative and miseducative quality. Finally, we interpreted the quality of the larger experience of engaging in this participatory investigation. Findings: Thematic findings included our experience of: (a) work knowing no bounds, including the time-intensive struggle of work-life balance, dictates of funding and employment, and challenges of juggling multiple roles; (b) feeling fortunate for opportunities to grow as lifelong learners, to have support systems, and to engage with children and youths; and (c) feeling in limbo due to challenges to PE, our transient positions, and our mental health. Conclusion: We interpreted the majority of our thematic experiences to be educative and as pushing us to grow academically in constructive directions. Objective conditions such as graduate programmes, supervisors, peers, and family were primarily credited for this. We interpreted the minority of our thematic experiences as miseducative and as distorting our academic growth in unconstructive directions. This was almost exclusively attributed to internal conditions such as our failure to adapt ourselves to the environment. The larger experience of engaging in this participatory investigation was perceived as educative and due to the objective conditions of our newly formed community and Dewey's theory. Our communal reflection on our experiences via Dewey's criteria stimulated growth and the desire to continue in, rather than retreat from, PE and academia. We suggest that all PE graduate students would benefit from the opportunity to engage with a community of peers in sustained, theory-guided reflection on the quality of their graduate experiences.